2016
DOI: 10.3418/jjam.30.89
|View full text |Cite
|
Sign up to set email alerts
|

Post void residual and lower urinary tract symptoms: A prospective study of related factors in the second trimester of pregnancy and the postpartum

Abstract: The aim of this prospective study is to assess factors related to post void residual (PVR) and lower urinary tract symptoms in the second trimester of pregnancy, and the postpartum of women who presented normal bladder function before and until the second trimester of their pregnancies and delivered vaginally. Methods Pregnant women planning vaginal delivery who presented no bladder function problems before the present pregnancy and until the second trimester of their pregnancies (PVR of less than 50 ml) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Tanaka et al also suggested that there are many women who have residual urine shortly after childbirth, and in the future it seems important to identify residual urine by ultrasound. Satoh, Goto, Herrera, Otsuka, and Ishikawa () observed daily changes in postpartum residual urine volume by bladder scan. Satoh et al () reported that among 65 postpartum women, 12 (18.5%) on the first day and 20 (30.8%) on the third day had a residual urine of 150 mL or more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaka et al also suggested that there are many women who have residual urine shortly after childbirth, and in the future it seems important to identify residual urine by ultrasound. Satoh, Goto, Herrera, Otsuka, and Ishikawa () observed daily changes in postpartum residual urine volume by bladder scan. Satoh et al () reported that among 65 postpartum women, 12 (18.5%) on the first day and 20 (30.8%) on the third day had a residual urine of 150 mL or more.…”
Section: Discussionmentioning
confidence: 99%
“…Satoh, Goto, Herrera, Otsuka, and Ishikawa (2016) observed daily changes in postpartum residual urine volume by bladder scan. Satoh et al (2016) reported that among 65 postpartum women, 12 (18.5%) on the first day and 20 (30.8%) on the third day had a residual urine of 150 mL or more. And among 65 women, 47 (72.3%) on the first day after vaginal delivery have reported reduced bladder sensation.…”
Section: Definition and Prevalence Of Purmentioning
confidence: 99%